Analysis and Application of Indoor Fire Fighting Positioning Technology Based on Inertial Navigation. Issue 2 (October 2020) - Deng, Jun; Zhao, Jiaxiang; Wang, Weifeng; Sheng, Youjie
Abstract: In recent years, all kinds of complex buildings have increased rapidly, and the difficulty of fire rescue has increased significantly. Therefore, it is of great significance to improve the level of fire rescue to study the precise positioning technology that can be applied to the firefighter's room in all kinds of complex scenes. In this paper, several common indoor positioning technologies are summarized and introduced, and their positioning principles, positioning accuracy, use scenarios and other parameters are analyzed by analogy. The application of inertial navigation positioning technology in the positioning of firefighters in complex indoor environment is discussed and verified by experiments. According to the analysis results, the key technologies for the indoor positioning of firefighters are optimized. The analysis and research in this paper can provide theoretical support for improving the positioning of firefighters in the room.